(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article investigates the conditions and prerequisites for involving students in the educational process. The mechanisms of interaction between teachers and students in the process of reading lecture courses based on innovative technologies are analyzed.